Improving the Worlds Largest Online Grocery Catalog : a Data Science Story - Salon, Data; Salon, Data (Data Science Salon, 2019)
Presented by Ishant Nayer, Sr Data Scientist at Instacart Being a data-driven company, Instacart realizes the power of good quality data. While trying to maximize the efficiency of data consumption by all work streams such as recommendation systems and availability systems, we are trying to make our Catalog the best in the world by delivering precise information to all our end-users including shoppers and consumers. This session will cover the following areas: 1. How we used data science to auto-detect inconsistencies in the data attributes of millions of items comprising the Catalog, in real-time. 2. How we defined and utilized North Star metrics to optimize data quality of our Catalog 3. Different approaches being used to deliver a great customer experience.